Proofs for the Existence of God: A Discussion with Richard Swinburne - Swinburne, Richard; Meichanetsidis, Vasileios (Conatus - Journal of Philosophy, 2024)
Over the last 50 years, the English philosopher Richard Swinburne (b. 1934) has been a very influential proponent of philosophical arguments for the existence of God (natural theology). His major philosophical contributions lie in the areas of philosophy of science and philosophy of religion. From a general philosophical point of view, Swinburne stimulated much discussion with his early work in the philosophy of religion. He has also played a role (a) in the recent debate over the mind-body problem, and (b) in the debate on libertarian free will. Swinburne is also noted as one of the foremost current Christian apologists, arguing that faith in Christian God is rational and coherent in a rigorous philosophical sense. My discussion with Richard Swinburne revisits the analytic and non-analytic philosophy of religion. Above all, however, it aims at shedding light on Swinburne’s thought regarding some important philosophical issues, such as the Kantian arguments on the existence of God, the relationship between ratio and one’s immediate experience of God (empireia), “strong possibilities” the problem of the existence of evil in the world, but also the theological significance and value of Orthodoxy in contrast to other Christian creeds or even religions.